THE RELATIONSHIP OF PERSONAL HYGIENE WITH THE INSIDENT OF SCABIES IN ADOLESCENTS - Khoerun Nisa Fitri Fitri; Johan Budhiana; Lia Novianty (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Scabies is an infectious disease that is at risk for people with weak immune systems and living in unfavorable environments. The factor that influences the incidence of scabies is personal hygiene. The aim of this research was to determine the relationship between personal hygiene and the incidence of scabies in adolescents at the Al Istiqomah integrated Islamic boarding school in the working area of ​​the UPTD Gunungguruh Community Health Center, Sukabumi Regency. Scabies is a skin disease caused by the Sarcoptes Scabiei hominis variant. Personal hygiene is an action in maintaining individual cleanliness and health with the aim of achieving physical and psychological well-being. Type of correlational research with a Cross Sectional approach. The population in this study were teenagers at the Al Istiqomah integrated Islamic boarding school with a sample of 126 respondents. The sampling technique was simple random sampling. Data collection method through questionnaires. Data analysis used the Chi-Square Test. The results showed that the majority had good personal hygiene (76.2%) and did not experience scabies (57.9%). There is a relationship between personal hygiene and the incidence of scabies with a p-value of 0.000. The conclusion is that there is a relationship between personal hygiene and the incidence of scabies in teenagers. The efforts made by the Gunungguruh Community Health Center include providing education to all students using easy-to-understand media that can be carried out in everyday life.